Analisis Penggunaan Scilab dan IPCV dalam Pengolahan Citra Digital (Image Processing) - Rajin Nahampun; Norita Sinaga; Afiani Agus Abdillah (OKTAL : Jurnal Ilmu Komputer dan Sains, 2025)
Digital image processing is a crucial area of information technology, widely applied in medicine, security, robotics, and industry. One software tool for image processing is Scilab, an open-source numerical computing environment. Supported by the IPCV (Image and Video Processing & Computer Vision) toolbox, Scilab can perform various basic image processing operations, such as image reading, color conversion, contrast enhancement, and edge detection. This paper demonstrates the implementation of image processing using Scilab 2025.1.0 with the IPCV toolbox. Test images were read, converted to grayscale, contrast enhanced using histogram equalization, and edge detection using the Sobel and Canny operators. The results demonstrate that Scilab + IPCV effectively processes images with a simple interface and easy-to-understand processes. This system is ideal for use as a learning tool for students and novice researchers in image processing.